Synthesis of sulfonyl chlorides and thiosulfonates from H2O2–TiCl4 - Bahrami, Kiumars; Khodaei, Mohammad M.; Khaledian, Donya (Tetrahedron letters, 2012)
A new method is described for the oxidative chlorination of thiols to sulfonyl chlorides using titanium tetrachloride in combination with the oxidant hydrogen peroxide. Direct conversion of thiols into their corresponding thiosulfonates is also reported. Good to excellent yields, short reaction times, high efficiencies, cost-effectiveness, and, facile isolation of the desired products make the present methodology a practical alternative. (C) 2011 Elsevier Ltd. All rights reserved.